2004
DOI: 10.1128/cdli.11.5.969-976.2004
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-Anchored CD14 Is Important for Induction of Interleukin-8 by Lipopolysaccharide and Peptidoglycan in Uroepithelial Cells

Abstract: We investigated the induction of interleukin-8 (IL-8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 35 publications
3
24
1
Order By: Relevance
“…The quantitative nature of the PCR was validated by the linearity of the determination curve at various concentrations of RNA. In accordance with previous papers, the primer sets used were as follows: cystatin A (37), cystatin C (40); TLRs 1,5,6,7,8,9, and 10 (13); TLR2, TLR4, and glyceraldehyde-3=-phosphate dehydrogenase (GAPDH) (33); and TLR3 (28). Primer sets for adenosine receptors A 1 , A 2A , A 2B , and A 3 were as described by Schön et al (31), except for the reverse primer of A 2A (5=-CTGCTTCAGCTGTCGTCGC G-3=).…”
Section: Methodsmentioning
confidence: 99%
“…The quantitative nature of the PCR was validated by the linearity of the determination curve at various concentrations of RNA. In accordance with previous papers, the primer sets used were as follows: cystatin A (37), cystatin C (40); TLRs 1,5,6,7,8,9, and 10 (13); TLR2, TLR4, and glyceraldehyde-3=-phosphate dehydrogenase (GAPDH) (33); and TLR3 (28). Primer sets for adenosine receptors A 1 , A 2A , A 2B , and A 3 were as described by Schön et al (31), except for the reverse primer of A 2A (5=-CTGCTTCAGCTGTCGTCGC G-3=).…”
Section: Methodsmentioning
confidence: 99%
“…Reverse transcription-PCR (RT-PCR) was performed by using the OneStep RT-PCR kit (Qiagen). mRNA levels of TLR2, TLR4, and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), used as a control, were determined as previously described (27). The quantitative nature of the RT-PCR was validated by the linearity of the determination curve at various concentrations of RNA.…”
mentioning
confidence: 99%
“…Flow cytometry was performed by using a FACSCalibur (Becton Dickinson, San Jose, CA) as previously described (27,37). Phycoerythrin-labeled mouse monoclonal antibodies against TLR2 (clone TL2.1), TLR4 (HTA125), and CD14 (61D3), and their isotype controls, phycoerythrinlabeled mouse monoclonal immunoglobulin G1 (IgG1) and IgG2a, were purchased from eBioscience (San Diego, CA).…”
mentioning
confidence: 99%
“…The different response to sCD14 observed by us and by Asai et al (2003a) could be due to a difference in the contamination degree and molecules in the peptidoglycan used by the two groups. Shimizu et al (2004) showed that cells expressing mCD14 did not need exogenous sCD14 for TLR2-mediated peptidiglycan signalling. This result is consistent with our observation that peptidoglycan stimulated cells in an sCD14-independent manner.…”
Section: Discussionmentioning
confidence: 99%